2011
DOI: 10.1121/1.3531934
|View full text |Cite
|
Sign up to set email alerts
|

Hearing threshold estimation using concurrent measurement of distortion product otoacoustic emissions and auditory steady-state responses

Abstract: Both distortion product otoacoustic emissions (DPOAEs) and auditory steady-state responses (ASSRs) provide frequency-specific assessment of hearing. However, each method suffers from some restrictions. Hearing losses above 50 dB HL are not quantifiable using DPOAEs and their performance at frequencies below 1 kHz is limited, but their recording time is short. In contrast, ASSRs are a time-consuming method but have the ability to determine hearing thresholds in a wider range of frequencies and hearing losses. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…This study demonstrated that concurrent measurements are feasible in a relatively short duration of 11 min. Several studies have described methods for concurrently measuring DPOAEs and ASSRs (Purcell et al, 2003;Oswald et al, 2006;Rosner et al, 2011;Wittekindt et al, 2014). However, to the authors' knowledge, the present study is the first to report concurrent measurements of TEOAEs and of ASSRs for the purpose of examining contralateral suppression.…”
Section: A Feasibility Of Concurrent Measurementsmentioning
confidence: 83%
“…This study demonstrated that concurrent measurements are feasible in a relatively short duration of 11 min. Several studies have described methods for concurrently measuring DPOAEs and ASSRs (Purcell et al, 2003;Oswald et al, 2006;Rosner et al, 2011;Wittekindt et al, 2014). However, to the authors' knowledge, the present study is the first to report concurrent measurements of TEOAEs and of ASSRs for the purpose of examining contralateral suppression.…”
Section: A Feasibility Of Concurrent Measurementsmentioning
confidence: 83%
“…In conventional devices using clicks as stimulus, the measurement is restricted to 500–4,000 Hz but using chirp recordings are possible up to 6,000 Hz. Further high frequency solutions concerning otoacoustic emissions, auditory brainstem responses, and auditory steady‐state responses are in development (e.g., combining distortion product otoacoustic emission recordings with auditory steady‐state response measurements reaching frequencies up to 6,000 Hz) …”
Section: Selected Ototoxic Drugsmentioning
confidence: 99%
“…One way to estimate the threshold of cochlear hearing impairment up to a hearing loss of about 50 dB HL is the Janssen “scissor” paradigm [ 12 ]. This special DPOAE examination is currently used sporadically, sometimes in combination with the auditory steady state response (ASSR) [ 39 ], [ 40 ]. The detection of OAEs in hearing impairment can distinguish between inner ear hearing impairment and auditory synaptopathy/neuropathy; an OAE measurement should therefore always be made if more severe hearing impairment is suspected [ 29 ].…”
Section: Diagnostics and Causes Of Early Childhood Hearing Disordermentioning
confidence: 99%